2008
DOI: 10.4319/lo.2008.53.3.1025
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen biogeochemistry of submarine groundwater discharge

Abstract: To investigate the role of the seepage zone in transport, chemical speciation, and attenuation of nitrogen loads carried by submarine groundwater discharge, we collected nearshore groundwater samples (n 5 328) and examined the distribution and isotopic signature (d 15 N) of nitrate and ammonium. In addition, we estimated nutrient fluxes from terrestrial and marine groundwater sources. We discuss our results in the context of three aquifer zones: a fresh groundwater zone, a shallow salinity transition zone (STZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
201
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 50 publications
6
201
1
Order By: Relevance
“…This may be due to rapid biological nitrogen uptake in the summer when any 496 the winter nitrogen residence time in the surface water is much longer, allowing build-up 498 and more even distribution within the bay (Valiela et al, 1992). Another explanation is 499 that the nitrate+nitrite concentration is different in fresh and recirculated groundwater and 500 when the relative magnitude of fresh and recirulated groundwater discharge changes so 501 does the nitrate+nitrite concentration of the surface water (Kroeger and Charette, 2008). 502…”
Section: Sgd Rates Derived From Tracers 217mentioning
confidence: 99%
“…This may be due to rapid biological nitrogen uptake in the summer when any 496 the winter nitrogen residence time in the surface water is much longer, allowing build-up 498 and more even distribution within the bay (Valiela et al, 1992). Another explanation is 499 that the nitrate+nitrite concentration is different in fresh and recirculated groundwater and 500 when the relative magnitude of fresh and recirulated groundwater discharge changes so 501 does the nitrate+nitrite concentration of the surface water (Kroeger and Charette, 2008). 502…”
Section: Sgd Rates Derived From Tracers 217mentioning
confidence: 99%
“…SGD flows with an average rate of 1.4 Â 10 À5 m s À1 (156 cm d À1 ) and an average salinity of 5& (ranging from 0.6& to 14&). As suggested by Kroeger and Charette (2008), much of the fresh groundwater ultimately discharges as brackish water due to significant mixing with saline porewater in the shallow beach sediments prior to discharge. Unlike other SGD studies of Waquoit Bay using seepage meters (Michael et al, 2003;Sholkovitz et al, 2003), the predicted seepage face does not include offshore seepage areas but is restricted to the beachface, delimited by the position of the seaward piezometer PZ-12.…”
Section: Flow Dynamicsmentioning
confidence: 99%
“…5b), indicating that the conditions for effective denitrification are not met. In their analysis of the nutrient data collected in spring 2003 from the same sampling transect, Kroeger and Charette (2008) propose the occurrence of denitrification of the NO 3 À in the freshwater plume prior to its discharge, based on the substantial observed loss of NO 3 À around PZ-5. In our case, however, the peak NO 3 À concentration increases from PZ-11 to PZ-3, and stays rather elevated in intertidal piezometer PZ-5 where it is partially discharged.…”
Section: Nitrogen Dynamicsmentioning
confidence: 99%
“…Other studies highlight that biogeochemical processes occurring in a STE can attenuate high N and P in contaminated terrestrial groundwater prior to discharge to the coastal ocean [Addy et al, 2005;Kroeger and Charette, 2008;Santoro et al, 2008]. For example, attenuation of nitrate contamination in terrestrial groundwater by denitrification has been observed in STEs [Loveless and Oldham, 2010;Weinstein et al, 2011;Erler et al, 2014], resulting in non-conservative net nitrate removal ( Figure 4A).…”
mentioning
confidence: 99%
“…N2O is formed as a byproduct during nitrification or as an intermediate product during denitrification. With field investigations [Kroeger and Charette, 2008;Santos et al, 2009d] and modelling [Spiteri et al,35 2008a] indicating that both denitrification and nitrification are important in STEs. SGD may be a two-fold source of N2O to surface waters.…”
mentioning
confidence: 99%